Biocatalytic Potential of Native Basidiomycetes from Colombia for Flavour/Aroma Production (2020)
ABSTRACT : Aromas and flavours can be produced from fungi by either de novo synthesis or biotransformation processes. Herein, the biocatalytic potential of seven basidiomycete species from Colombia fungal strains isolated as endophytes or basidioma was evaluated. Ganoderma webenarium, Ganoderma chocoense, and Ganoderma stipitatum were the most potent strains capable of decolourizing β,β-carotene as evidence of their potential as biocatalysts for de novo aroma synthesis. Since a species’ biocatalytic potential cannot solely be determined via qualitative screening using β,β-carotene biotransformation processes, we focused on using α-pinene biotransformation with mycelium as a measure of catalytic potential. Here, two strains of Trametes elegans—namely, the endophytic (ET-06) and basidioma (EBB-046) strains—were screened. Herein, T. elegans is reported for the first time as a novel biocatalyst for the oxidation of α-pinene, with a product yield of 2.9 mg of cis-Verbenol per gram of dry weight mycelia used. The EBB-046 strain generated flavour compounds via the biotransformation of a Cape gooseberry medium and de novo synthesis in submerged cultures. Three aroma-producing compounds were identified via GC–MS—namely, methyl-3-methoxy-4H-pyran-4-one, hexahydro-3-(methylpropyl)-pyrrolo[1,2-a]pyrazine-1,4-dione, and hexahydro-3-(methylphenyl)-pyrrolo[1,2-a]pyrazine-1,4-dione.